ANALISIS KUALITAS LAYANAN PORTAL MEDIA ONLINE KOTA JOGJA.COM TERHADAP PENGGUNA AKHIR MENGGUNAKAN METODE WEBQUAL 4.0 - Susanti, Erma; Septrisulviani, Ririn (JURNAL GAUNG INFORMATIKA, 2018)
Online media portal kotajogja.com is one of the online news products produced by PT. Integra Innovation Indonesia. To know the extent to which the quality of news generated based on the perception of the user or online news reader, it is necessary to analyze the quality of website services. One method that can be used for website quality analysis is using WebQual 4.0. The WebQual 4.0 method is a method of measuring website quality based on end user perceptions. This method is based on 3 dimensions: usability, information quality and interaction quality. In addition to using WebQual 4.0, Likert scales are also used as research intervals.The process of analysis in this study using sample withdrawal stages of 96 people consisting of 48 student respondents and 48 workers respondents. Data collection of respondents using an online questionnaire. Prior to the data collection process, validity test was performed using Bivariate Pearson formula and reliability test using Alpha Cronbachs formula. The assessment process in this study using Likert scale with 5 interval scale. The last step is analysis by WebQual method and Chi Square test. The results of the calculation of the overall average showed 3.73 with the interpretation of "MEMUASKAN" (SATISFACTORY). Only, there is one item of quality interaction dimension about the trust of storing information that should be improved. Chi Square test results known that affecting the level of respondent satisfaction is the quality ofuse, while the quality of information and the quality of interaction does not significantly affect the user satisfaction website jogja.com.